CuO Nanoparticles as An Efficient Heterogeneous Catalyst for the 1, 3‐Dipolar Cycloaddition of Dicarbonyl Compounds to Azides. Issue 22 (13th June 2018) - da S. Dias, Cássio; de M. Lima, Thiago; Lima, Carolina G. S.; Zuekrman‐Schpector, Julio; Schwab, Ricardo S.
Abstract: Substituted 1, 2, 3‐triazoles are important heterocyclic molecules with applications in diverse research areas. The organocatalytic (3+2) cycloaddition reaction of azides with active methylene compounds has proven to be a powerful strategy for the synthesis of a variety of 1, 2, 3‐triazoles with different substituents. However the reported methods in the literature, commonly used a homogenous organocatalyst. Considering this point, here we have reported a novel heterogeneous protocol for the synthesis of 1, 4, 5‐trisubstituted 1, 2, 3‐triazoles by reaction of different dicarbonyl compounds with aryl azides catalyzed by copper oxide nanoparticles under microwave irradiation. The important features of this methodology are high yield products, short reaction times and recyclability of the CuO catalyst. Abstract : The organocatalytic (3+2) cycloaddition reaction of azides with active methylene compounds has proven to be a powerful strategy for the synthesis of a variety of 1, 2, 3‐triazoles with different substituents. However the reported methods in the literature, commonly used a homogenous organocatalyst. Considering this point, here we have reported a novel heterogeneous protocol for the synthesis of 1, 4, 5‐trisubstituted 1, 2, 3‐triazoles by reaction of different dicarbonyl compounds with aryl azides catalyzed by copper oxide nanoparticles under microwave irradiation.